Pelaksanaan Ekstrakurikuler Hizbul Wathan untuk Membangun Karakter Cinta Tanah Air - Okky Putra; Zuhdiyah, Zuhdiyah; Rohmadi, Rohmadi (PAI RAFAH, 2025)
This research is titled "The Implementation of Hizbul Wathan Extracurricular Activities to Build a Love for the Homeland Character." The objective of this research is to understand how the implementation of the Hizbul Wathan extracurricular activity builds a love for the homeland character. And to determine the supporting and inhibiting factors in the implementation of the Hizbul Wathan extracurricular to build a love for the homeland character. The research methodology used in this study employs a qualitative approach with the type of research being Field Research. The techniques for data collection in this study include interviews, observations, and documentation. Meanwhile, the data analysis techniques in the research are data reduction, data presentation, and conclusion drawing. The research results indicate that the implementation of the Hizbul Wathan extracurricular activities is indeed being carried out. The instructors carry out activities related to the character of love for the homeland, such as ceremonies or flag-raising, nature explorations, camping, social and environmental service, and pioneering. Regarding the supporting and inhibiting factors of the Hizbul Wathan extracurricular activities in building a love for the homeland character, they include the facilities provided by the school and competition activities that can boost students' enthusiasm and interest. On the other hand, the inhibiting factors include bad weather conditions, such as rain, and the lack of Hizbul Wathan extracurricular advisors.